A comparison of metal distribution in surface soil between wetland and farmland in the Sanjiang plain - Yang Yu; Chao Zhan; Yunzhao Li; Di Zhou; Junbao Yu; Jisong Yang (HydroResearch, 2023)
The transformation from wetland to farmland is in vigorous process to gain more grain production. Meanwhile, restoring wetland from farmland is going on due to the important ecological function of wetland. To understand the ecological risk which might happen in these transform processes, the 18 kind of metals and SOM were analyzed in 25 wetland sites and 7 farmland sites from Sanjiang Plain. Results showed that the concentration of most metals in wetland was lower than that in farmland in generally and SOM was higher in wetland. According to Geo-accumulation index, there were no pollution for most metals. Metal pollution risk in farmland was generally higher than that in wetland except Cu and Zn. Parent rocks, flooding conditions and vegetation types were the main metal sources for wetland. For farmland, anthropogenic activities were the major metal sources. Metal distribution should be taken seriously to avoid metal pollution when land use was changed.